Classification tools for business models: Status quo, comparison, and agenda - Thorsten Schoormann; Julia Schweihoff; Ilka Jussen; Frederik Möller (Electronic Markets, 2023)
To sustain competitive advantage in dynamic business environments, organizations have to constantly adapt, innovate, and recombine their business models. As some configurations of business model design options are more successful than others, it is crucial to have a holistic understanding of the (current) solution space of those options and their dependencies. To be aware of and manage the set of possible design options, one can rely on classification tools, including taxonomies, typologies, and classification schemes. Given the availability of several tool types, different underlying assumptions for each type need to be considered when designing and applying a tool. Following a descriptive literature review approach, this paper structures the diverse body of classification research by presenting a repository of tools and deriving an analytical grid to disclose the similarities and differences between selected tool types. Thereby, this paper (1) raises awareness for the plurality of tools and their underpinning concepts, (2) provides a status quo overview across tool types, and (3) derives design-relevant knowledge for the tools, points to current challenges, and paves the ground for future research on the building, evaluation, and use of this class of tools.
Keywords: M13; O30; 620; Business model; Taxonomy; Typology; Classification; Design options